Giant phonon anomalies in the proximate Kitaev quantum spin liquid α-RuCl3 - Haoxiang Li (Nature Portfolio, 2021)
It was recently proposed that the coupling between phonons and fractional excitations of a Kitaev quantum spin liquid can be detected in its phonon dynamics. Here, the authors report signatures of this coupling, manifested in low-energy phonon anomalies measured by inelastic X-ray scattering with meV resolution.